The Human Factor in Digital Transformation: An Empathy-Driven Approach to Change Management in India’s IT and ITES Organizations - Bose, Joie (Digital Repository of Theses - SSBM Geneva, 2025)
The original empirical research on human factor in digital transformation change management in the India’s ITES sector, investigated the role of human factors. The research aimed to understand how leadership empathy and specifically dimension of psychological safety influence the employees towards change-adoption behavior and change methods that help the IT organization transition from Industry 4.0 to Industry 5.0. Results showed strong positive correlations between change adoption and factors such as employee readiness, empathetic leadership and organizational support. Regression analysis indicates that leadership empathy significantly predicts change adoption. Thematic analysis found primary and secondary themes. Primary themes include - human decision making vs. automation decision making, change dynamics and process, leadership and organizational culture, value addition and continuous improvement, skill evolution and technical knowledge. Secondary themes include - real time feedback and communication, diversity and inclusion, ethical considerations with empathy, iterative change, continuous training interventions. The research concluded that holistic approach integrates humancentric values with technological advancements is essential for change management to be successful and an empathetic leadership and a supportive, psychologically safe environment is crucial for enhancing employee readiness, reducing resistance to change, and driving Industry 4.0 to Industry 5.0 transformational journeys.